Issues of Truth and Correctness vs. Rhetoric in Media Discourse - Ostrowski, Marek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Following Niklas Luhmann, the author assumes that communication creates social systems. The system therefore influences the nature of communication. The impact of rhetoric on media discourse can be understood as a result of the strategy adopted by the system. What follows from the above assumption is a discussion of the notion of truth which is fundamental to media philosophy. Systems, in their adopted strategies, affect the media and use persuasion in a way that is remote from the treatment of the truth as an idea or as a condition of an ethical nature.